2020
DOI: 10.3390/coatings10090849
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of a Ni–Cr–Mo Alloy Coating Fabricated by Laser Cladding in a Simulated Sulfuric Acid Dew Point Corrosion Environment

Abstract: For this study, aimed at proposing a potential direction to prevent sulfuric acid dew point corrosion, a Ni–Cr–Mo alloy Hastelloy C22 coating was fabricated by coaxial laser cladding technology. The phase composition, microstructure, and corrosion behavior in a simulated sulfuric acid dew point corrosion environment were investigated and compared with a Hastelloy C22 alloy, a titanium alloy TC4, and 09CrCuSb steel (ND). The results showed that the phase composition of the C22 coating is essentially similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 59 publications
5
17
1
Order By: Relevance
“…The Ni–xCr–Mo laser coatings were fabricated using a self-assemble coaxial laser-cladding device equipped with a 2000 W high-power fiber laser (ZKZM-2000, zKzM Laser Technology Co., Ltd., Xi’an, China), a self-designed coaxial powder-feeding nozzle that ejected three powder streams, and an argon shielding system. The schematic of the laser-cladding process is illustrated in [ 27 ]. During the fabrication of laser-cladding coatings, the 20G steel substrate with dimensions of 20 × 20 × 5 cm was polished and cleaned with acetone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ni–xCr–Mo laser coatings were fabricated using a self-assemble coaxial laser-cladding device equipped with a 2000 W high-power fiber laser (ZKZM-2000, zKzM Laser Technology Co., Ltd., Xi’an, China), a self-designed coaxial powder-feeding nozzle that ejected three powder streams, and an argon shielding system. The schematic of the laser-cladding process is illustrated in [ 27 ]. During the fabrication of laser-cladding coatings, the 20G steel substrate with dimensions of 20 × 20 × 5 cm was polished and cleaned with acetone.…”
Section: Methodsmentioning
confidence: 99%
“…During the fabrication of laser-cladding coatings, the 20G steel substrate with dimensions of 20 × 20 × 5 cm was polished and cleaned with acetone. Following prior research [ 27 , 28 ], the laser-cladding parameters were set as follows: beam spot was 1.4 mm in diameter, laser power was 2000 W, overlap ratio was 40%, laser scan speed was 8 mm/s, and the flow rate of argon was 5 L/min. In order to reduce the negative effect of dilution rate on the corrosion resistance of the laser coatings, the thickness of the laser coating prepared on the surface of the 20 G substrate by the multitrack cladding process was set at 5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…LAM to add thin layers of metal materials under the guidance of computer to complete the processing of workpiece with special shapes, this technology eliminates the need of expensive moulds or casting moulds and simplifies the complex steps of traditional casting [6,7]. However, metallurgical defects, pores, and cracks are found in LAM workpiece due to the particularly heating and cooling rate of the technology, and dendrites, topological close-packed phase (TCP), and carbide are easily generated in the LAM materials as well, which will affect the corrosion resistance of LAM materials [8][9][10][11]. Hu et al [12] reported the influence of Laves phase on the mechanical properties and corrosion resistance of Inconel 625, and the high brittleness of Laves phase created cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been proposed to improve the corrosion resistance of steel in marine environments [9][10][11]. These methods include the addition of corrosion inhibitors [12,13], coatings [14][15][16], and alloying elements [13,17,18].…”
Section: Introductionmentioning
confidence: 99%